Budaya Organisasi di Story Teller Bersukaria Walk Semarang - Nadya Alma Tusada; Af’idatul Lathifah; Eko Punto Hendro (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
Tourism has an important aspect in the growth and development of a country. In its development, tourism is needed by the community as a means of entertainment. The progress of tourism can also be seen from the many variations of tourism services, one of which is the Bersukaria Walk Semarang which is a sub product of the Bersukaria Tour. Packaging tourism services on foot and telling stories behind buildings is a new form of tourism. In carrying out its activities, a company that has a good organizational culture will be reflected in the work attitude of its members, in this Merukaria Walk it is called a Story Teller. This research uses ethnographic research method with participatory observation, namely following the activities of Jalan Bersukaria every Saturday-Sunday and national holidays then conducting in-depth interviews and documentation. In carrying out their work, Story Teller applies attitudes that describe the company such as values and norms that are also applied by the captain or company leadership. The conclusion that can be drawn in this study is that leaders have an important role not only to instill values, norms, and make symbols as a characteristic of the company, but also rituals or activities designed to bring Story Tellers and leaders closer together. to build relationships with its members. Organizational culture has an important role to play for Story Teller, as created by Bersukaria Walk which formed Story Teller for discipline at times as well as customer-friendly attitude.